2014
DOI: 10.1111/jth.12484
|View full text |Cite
|
Sign up to set email alerts
|

Endogenous sex hormones and risk of venous thromboembolism in women and men

Abstract: To cite this article: Holmegard HN, Nordestgaard BG, Schnohr P, Tybjaerg-Hansen A, Benn M. Endogenous sex hormones and risk of venous thromboembolism in women and men. J Thromb Haemost 2014; 12: 297-305.Summary. Background: Use of oral contraceptives with estrogen and hormone replacement therapy with estrogen or testosterone are associated with increased risk of venous thromboembolism (VTE). However, whether endogenous estradiol and testosterone concentrations are also associated with risk of VTE is unknown. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
38
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 35 publications
7
38
2
3
Order By: Relevance
“…Similar results were reported by Holmegard et al 52 in the Copenhagen City Heart Study, including 4673 men representative for the adult Danish population. In line with these data, Mumoli et al 53 were unable to detect any difference in T and oestradiol levels between 63 patients with unprovoked deep venous thrombosis (DVT) and matched controls (table 3).…”
Section: Venous Thromboembolism Risksupporting
confidence: 90%
See 1 more Smart Citation
“…Similar results were reported by Holmegard et al 52 in the Copenhagen City Heart Study, including 4673 men representative for the adult Danish population. In line with these data, Mumoli et al 53 were unable to detect any difference in T and oestradiol levels between 63 patients with unprovoked deep venous thrombosis (DVT) and matched controls (table 3).…”
Section: Venous Thromboembolism Risksupporting
confidence: 90%
“…Two large population-based studies failed to find an association between endogenous T and VTE (table 3). 51 52…”
Section: Venous Thromboembolism Riskmentioning
confidence: 99%
“…However, there is also evidence that testosterone therapy may have protective endothelial actions. [8][9][10][11] Two large population-based studies 12,13 reported that endogenous testosterone levels were not associated with VTE. To date, no comparative studies examining an association between testosterone therapy and VTE have been reported.…”
mentioning
confidence: 98%
“…The Copenhagen City Heart Study, a prospective study of 4673 men, found no associations with extreme levels of endogenous T (defined as > 95th percentile) and elevated risk of deep venous thrombosis, pulmonary embolism, or recurrent VTE [Holmegard et al 2014]. Similarly, a prospective, population-based study of 1350 men aged 50-84 years yielded only 4.5 VTE events per 1000 person-years over 10.4 years of follow up with an insignificant HR of 1.06 (95% CI 0.83-1.35) [Svartberg et al 2009].…”
Section: Risk Of Cardiovascular Morbidity and Mortalitymentioning
confidence: 99%